The Practice of Environmental Journalism by Tribun Jateng On Reporting Illegal Mining In Batang Regency - Rochmawati, Novia; Pawito, Pawito; Hastjarjo, Sri (Journal of International Conference Proceedings, 2023)
The Environmental Issue has become a sensitive problem in Batang Regency. This is due to the fact that Batang Regency has several national-scale industrial projects, such as the Batang Integrated Industrial Estate.The development of these projects has also led to the increasing activities of illegal mining in Batang Regency. The issue of illegal mining has also become an environmental concern raised by Tribun Jateng. This research is expected to find out how the Tribun Jateng addresses this issue from the side of Environmental Journalism. Environmental journalism is a journalistic activity that reports on environmental issues and invites all parties to contribute to the environmental conservation movement. This study uses phenomenology theory which re-expresses the phenomenon experienced by someone directly and is then expressed again in a more understandable way. This research was found that journalists have an understanding of the definition of Environmental Journalism, and the issue of Illegal Mining is considered something that needs to be addressed together. Tribun Jateng journalists admit that there are many obstacles when reporting on this issue. Among them are many sources or related parties who are not willing to be interviewed. There are also several warnings not to report on illegal mining issues. The informants hope that with this reporting, more people will be aware of the losses caused by the impact of illegal mining. Thus, more decisive actions can be taken.